Functional and electron-microscopic changes after differential traction injury in the sciatic nerve of a rat - Soo-Hwan Byun; Kang-Min Ahn (SpringerOpen, 2021)
Abstract Background During maxillofacial trauma or oral cancer surgery, peripheral nerve might be damaged by traction injury. The purpose of this study was to evaluate functional and histomorphometric changes after traction nerve injury in the sciatic nerve of a rat model. Methods A total of 24 Sprague-Dawley rats were equally divided into three groups: unstretched (sham/control, group A), stretched with 0.7N (group B) and 1.5N (group C). Traction injury was performed for 10 min in B and C groups. Functional recovery of the sciatic nerve was evaluated by walking track analysis, toe spread test, and pinprick test 2 weeks after injury. The weight of gastrocnemius muscles of both sides was measured to evaluate weight ratio (ipsilateral/contralateral). Total number of axons, axon fiber size, myelin thickness, G-ratio, axon number/mm2, diameter of fiber, changes of longitudinal width, and formation of the edema and hematoma were evaluated by transmission electron microscopy. Results The sciatic function indexes were −11.48±4.0, −15.11±14.84, and −49.12±35.42 for groups A, B, and C, respectively. Pinprick test showed 3.0, 2.86±0.38, and 1.38±0.52 for A, B, and group C. Muscle weight ratios were 0.98±0.13 for group A, 0.70±0.10 for group B, and 0.54±0.05 for group C. There were significant differences in toe spread test, pinprick test, and muscle weight ratio between control group and experimental group (p<0.001). In the experimental group, fiber number, fiber size, G-ratio, fiber number/mm2, myelin thickness, diameter of fiber, and longitudinal width were decreased with statistical significance. Conclusion The present study demonstrated that the nerve traction injury in the rat sciatic nerve damaged the motor and sensory function and axonal integrity. The amount of functional nerve damage was proportional to the amount of traction power and dependent on the initial tensile strengths (0.7N and 1.5N).